The heart of darkness - Conrad, Joseph, 1857-1924; New Editions ([Hellinikon, Greece] : New Editions, 2000)
The story details an incident when Marlow, an Englishman, took a foreign assignment from a Belgian trading company as a ferry-boat captain in Africa. Although Conrad does not specify the name of the river, at this time Congo Free State, the location of the large and important Congo River, was a private colony of Belgium's King Leopold II. Marlow is employed to transport ivory downriver; however, his more pressing assignment is to return Kurtz, another ivory trader, to civilization in a cover up. Kurtz has a reputation throughout the region
Title from container
Keywords: Psychological fiction, English; Adventure stories, English